2013
DOI: 10.1093/tropej/fmt061
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Estimation of Body Surface Area in Under-5 Children with Non-Edematous Severe Acute Malnutrition

Abstract: Among seven equations, Mosteller is useful for BSA calculation in NE-SAM. SAM Mosteller modified equation (164.551 × [Ht × Wt](0.5)) has least error and can serve as best measure of BSA in SAM children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The smallest bias demonstrated for Boyd and Mosteller formulae in the present study have been reported in previous studies. [ 23 24 ] Like these previous studies, the present study shows that Mosteller and Boyd's formulae are more accurate for BSA estimation than others formulae. Although Boyd's formula slightly overestimate BSA and Mosteller's formulae underestimates BSA in the Nigeria children population as previously reported by El Edelbi et al .,[ 27 ] they maintained the most clinically acceptable and fairly constant degree of bias as children's age increases.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The smallest bias demonstrated for Boyd and Mosteller formulae in the present study have been reported in previous studies. [ 23 24 ] Like these previous studies, the present study shows that Mosteller and Boyd's formulae are more accurate for BSA estimation than others formulae. Although Boyd's formula slightly overestimate BSA and Mosteller's formulae underestimates BSA in the Nigeria children population as previously reported by El Edelbi et al .,[ 27 ] they maintained the most clinically acceptable and fairly constant degree of bias as children's age increases.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Chhapola et al . [ 23 ] recently showed that Mosteller's formula is more suitable for BSA estimation of children with non-edematous severe acute malnutrition than Boyd's formula, thus supporting earlier reports.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The Meban formula was developed from foetal research in 1983 and was used to estimate BSA in newborn infants. It has been shown to be very accurate in that age group . The Mosteller formula, which was first presented in 1987, is a simplified version of an earlier formula that was developed by Gehan and George and it has been reported to be promising in paediatric patients …”
Section: Methodsmentioning
confidence: 99%
“…To substitute direct measurements of the BSA, several empirical formulas have been derived for more than a century, initiated by the pioneering work of Meeh (43) in 1879 on thermoregulation and metabolism. Table 1 lists more than 50 formulas (43–93) found by literature search in chronological order, together with a short description of the study population. It should be noted that we have neglected approaches, focusing on a simplification of existing formulas for a quick use like in emergency medicine.…”
Section: Body Surface Areamentioning
confidence: 99%